2009
DOI: 10.1002/ijc.24695
|View full text |Cite
|
Sign up to set email alerts
|

EP300—A miRNA‐regulated metastasis suppressor gene in ductal adenocarcinomas of the pancreas

Abstract: Genetic and epigenetic alterations during development of pancreatic ductal adenocarcinomas (PDACs) are well known. This study investigates genetic and epigenetic data together with tumor biology to find specific alterations responsible for metastasis formation. Using 16 human PDAC cell lines in a murine orthotopic PDAC model, local infiltration and metastatic spread were assessed by standardized dissemination scores. The cell lines were further classified into 3 hierarchical groups according to their metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 50 publications
(76 reference statements)
5
93
2
Order By: Relevance
“…miR-194 has been reported to be involved in the regulation of pancreatic cancer metastasis 18 and miR-204 in pancreatic acinar cell carcinoma transformation and progression. 19 Cell adhesion …”
Section: Discussionmentioning
confidence: 99%
“…miR-194 has been reported to be involved in the regulation of pancreatic cancer metastasis 18 and miR-204 in pancreatic acinar cell carcinoma transformation and progression. 19 Cell adhesion …”
Section: Discussionmentioning
confidence: 99%
“…22 Both snoRNAs have been widely used as internal controls for quantitative RT-PCR. [23][24][25][26][27] The forward primers were as follows: SNORD44 (NR_002750.2), 5=-CCTGGATGATGATAGCAAATGCTG-3=; and SNORD48 (NR_002745.1), 5=-AGTGATGATGACCCCAGGTAACT-3=. …”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…Moreover, a growing number of miRNAs have been classified as oncogenes or tumor-suppressor genes (4,5). Over the past decade, an increasing number of studies have shown dysregulation of miRNA expression in numerous tumor types including esophageal (6), lung (7), liver (8), pancreatic (9), bladder (10), ovarian (11) and gastric cancer (12).…”
mentioning
confidence: 99%